Технологическая подготовка гибких производственных систем - Митрофанов С. П. Сергей Петрович; Куликов Д. Д. Дмитрий Дмитриевич; Миляев О. Н. Олег Николаевич; Падун Б. С. Борис Степанович; Митрофанов С. П. (Ленинград, Машиностроение, 1987)
Авт. указаны на обороте тит. л.